Instructional Quality in Geography–A Subject-Specific Secondary Analysis of the Saxon School Evaluation - Bienert, Natalie; Scholten, Nina; Mehren, Rainer (Journal of Geography Education, 2024)
Instructional quality is supposed to predict students’ learning success. Due to the lack of empirical evidence concerning instructional quality in geography, this study aims to capture the status quo of geography lessons in its dimensions as well as its influencing factors to generate first empirical insights. A data set containing 679 geography lessons comprise the basis of this secondary analysis. External raters evaluated the lessons using an observation sheet. Results indicate that, overall, the instructional quality of geography lessons is rather positive (M=3.53). A factor analysis shows six sub-scales of geographic instructional quality: classroom management, structure & clarity, consolidation, student-orientation, content-based involvement, and individualization of the learning process. Significant differences emerge between sub-scales, grades, and types of school.